Dental service sector and patient-reported oral health outcomes: Modification by trust in dentists - Song, Youngha; Santiago, Pedro; Nair, Rahul; Cho, Hyun-Jae; Brennan, David (Frontiers in Public Health, 2023)
Objective The study aimed to examine the association between patient-reported oral health outcomes and the dental service sector and trust in dentists. The possible interaction effect of trust on this association was also explored. Methods Randomly selected adults aged over 18 years living in South Australia were surveyed using self-administered questionnaires. The outcome variables were self-rated dental health and the evaluation outcome of the Oral Health Impact Profile. The dental service sector and the Dentist Trust Scale were included in bivariate and adjusted analyses with sociodemographic covariates. Results Data from 4,027 respondents were analyzed. Unadjusted analysis showed that poor dental health and oral health impact were associated with sociodemographic characteristics, including lower income/education, public dental service, and lower trust in dentists (p < 0.01). Adjusted associations were similarly maintained (p < 0.05) but attenuated with the loss of statistical significance, mainly in the trust tertiles. Lower trust in dentists in the private sector had an interaction effect, with a higher prevalence ratio of oral health impact (prevalence ratio = 1.51; 95% confidence interval, 1.06–2.14; p < 0.05). Conclusion Patient-reported oral health outcomes were associated with sociodemographic characteristics, the dental service sector, and trust in dentists. Implications for public health The inequality of oral health outcomes between dental service sectors needs to be addressed both independently and in association with covariates including socioeconomic disadvantage.